Rejection of an Application for Permission to Exchange (Ruislag) Waqf Land in the Perspective of Maslahah (Case Study of Waqf Land in Bugis Village, Sesetan, Sidakarya, South Denpasar District, Denpasar City, Bali Province) - Musthafa; Luqman bin Haji Abdullah; Norhidayah binti Pauzi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The exchange (ruislag) of waqf land with other land was allowed in Islam and has been regulated in Indonesian legislation. Every implementation of waqf land exchange in Indonesia must first apply for permission to the Minister of Religious Affairs through the Ministry of Religious Affairs with the stages of checking and assessment from the regional to the central level. It must get a recommendation from the Indonesian Waqf Board. In its implementation, there was a waqf land exchange application that has received a recommendation from the Indonesian Waqf Board, but did not receive permission from the Minister of Religious Affairs, namely the case of an application for permission to exchange waqf land located in Bugis Sesetan Sidakarya village, South Denpasar sub-district, Denpasar city, Bali province. The rejection of the application has caused the waqf land to be unused in following with the waqf agreement and its condition has been neglected until now. Therefore, this research was conducted to evaluate whether the rejection of the application for permission to implement the land exchange provides maslahah to the waqf property. This type of research was literature research, this research used a qualitative approach with descriptive methods. The data collection technique in this research was documentation, which looked for data on matters or variables related to the application for permission to exchange waqf land in Bugis village from a maslahah perspective from the sources of books, articles, journals and research reports, then analysed using the content analysis method. The results showed that the application for permission to exchange waqf land in Bugis village should be rejected. Although the replacement land has the potential to be developed productively, because the value of the replacement land was lower than the waqf land, the application for permission to exchange is more maslahah to be rejected.